Factors Improving the Effectiveness of Mentoring In ThePractical Training of the Midwifery Students - Atanasova, Zdravka; Miteva, Kremena (International Journal of Scientific Research and Management (IJSRM), 2025)
Mentoring in the practical training of midwifery students midwifery students is closely related to their professional development and improvement. The mentor is responsible for the practical activities of the trainees, monitors their professional formation, maintains the quality of training and the health care provided.Objective: This scientific report aims to identify the factors influencing the effectiveness of mentoring in the clinical practical training of students in the specialty "Midwifery".Material and methods:Between October 2024 and January 2025, the opinions of a total of 67 practicing midwives. An anonymous questionnaire was used via Google Forms.Conclusion and findings: Effective mentoring in the practical training of midwifery students requires well-planned training, including organization, mentoring support for students, and an appropriate level of control. The study identified the following leading factors for improving the supervision and practical training of midwifery students: the student being prepared and taking responsibility for his or her own learning; solid professional experience and skillful supportive guidance of the mentor; small number of trainees in a group; support from midwifery colleagues indirectly and informally involved in the practical training; regular communication and collaboration with responsible university lecturers. The analysis of the results obtained and our own long-term pedagogical experience allow us to differentiate the factors that strengthen mentoring in the practical training of students in the specialty "Midwifery" in four areas: cooperation with the training institution; conditions of the work environment; opportunity for professional and personal development and affirmation